Moderating effect of instrumental activities of daily living on the relationship between loneliness and depression in people with cognitive frailty - Yafang Zhao; Xiaopeng Huo; Hongdi Du; Xiaoxing Lai; Zhen Li; Zhiyuan Zhang; Longfei Yang (BMC Geriatrics)
Abstract Background The identification of depression and loneliness among people with cognitive frailty (CF) could prevent negative psychological and physical health outcomes. Few studies have focused on physical and mental health together, and little is known about the role of daily activity in the association between depression and loneliness among elderly individuals with CF. Objectives To determine the positive effect of loneliness on depression among community-dwelling older adults with CF as well as the moderating effect of instrumental activities of daily living (IADL) on this association. Design, setting, participants, and measurements This cross-sectional study included 529 adults aged 65 years and older from a community-dwelling population who were screened for CF and was conducted from July 2023 to December 2023. The participants were assessed via validation instruments for the following main variables: Short-form Geriatric Depression Scale, Loneliness Questionnaire, Athens Insomnia Scale, Instrumental Activities of Daily Living (IADL), Social Support Scale, and sociodemographic characteristics. The participants were classified as having reversable CF (RCF) or potentially reversable CF (PRCF). Results The IADL, depression, insomnia, and loneliness scores were lower among individuals with RCF than among individuals PRCF. The moderating effect of IADL scores shows that the relationship between loneliness and depression has a steeper and positive slope when lower levels of IADL exist, compared with a straight line when there are higher levels of IADL, for this case, the line is less steep and showed negative association. Conclusions The integrity of physical and social connections has a protective effect on the mental health of elderly people with CF. It is necessary to pay attention to disability and loneliness among elderly individuals. Targeted interventions for improving physical activity and social participation seem to be practical and feasible solutions to alleviate depressive symptoms.